The role of germinal centers for antiviral B cell responses. - Bachmann, M (1998)
Germinal centers (GCs) are crucially involved in T cell-dependent B cell responses. B cells rapidly proliferate within GCs and their Ig variable region genes undergo hypermutation. Cognate T helper cells and antigen presented in native form on follicular dendritic cells (FDCs) select B cells expressing high-affinity Igs, leading to affinity maturation and the generation of memory B cells. In addition to these well-established functions of GCs, this article presents evidence that they also play a crucial role for the maintenance of specific memory Ig titers and for the prevention of viral antibody escape mutants.